Polysaccharide production by kefir grains during whey fermentation - Rimada, Pablo Sebastián (2002)
Fermentation of deproteinised whey with kefir grains CIDCA AGK1 was studied focusing on polysaccharide production from lactose. Kefir grains were able to acidify whey at different rates depending on the grain/whey ratio. During fermentation, kefir grains increased their weight and a water-soluble polysaccharide was released to the media. Exopolysaccharide concentration increased with fermentation time, reaching values of 57·2 and 103·4 mg/l after 5 days of fermentation in cultures with 10 and 100 g kefir grains/l, respectively. The polysaccharide fraction quantified after fermentation corresponded to the soluble fraction, because part of the polysaccharide became a component of the grain. Weight of kefir grains varied depending on the time of fermentation. Polysaccharide production was affected by temperature. Although the highest concentration of polysaccharide in the media was observed at 43 °C at both grain/whey ratios, the weight of the grains decreased in these conditions. In conclusion, kefir grains were able to acidify deproteinised whey, reducing lactose concentration, increasing their weight and producing a soluble polysaccharide.